2017
DOI: 10.3390/ijms18050949
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and Apoptotic Potential of Cyanidin-Based Anthocyanins on Melanoma Cells

Abstract: Elderberries are known for their high anthocyanins content, which have been shown to possess anti-proliferative and anti-cancer effects. Anthocyanins enriched extract (AEE) was obtained from elderberries and was characterized by LC/DAD/ESI-MS analysis. Five cyanidin-based anthocyanins were identified, among which Cy-3-O-samb was the major compound (51%). The total anthocyanins content of AEE was 495 mg Cy-3-O-samb/100 g FW. AEE inhibited proliferation of metastatic B16-F10 murine melanoma cells, in a concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
(41 reference statements)
0
19
0
1
Order By: Relevance
“…To find an effective natural compound that inhibits the NF-κB signaling pathway, IKKβ kinase activity was analyzed with an in-house natural product library, and CyCl was found as a potential candidate for reducing IKKβ phosphorylation. Recently, an anthocyanins-enriched extract from elderberries, in which five cyanidin-based anthocyanins were identified, inhibited proliferation and induced apoptosis in melanoma cells [33]. Cyanidin-3-O-glucoside, a cyanidin derivative, inhibited NF-κB signaling molecules and had a protective effect through activation of the Nrf2 pathway in intestinal epithelial cells exposed to TNF-α [34].…”
Section: Discussionmentioning
confidence: 99%
“…To find an effective natural compound that inhibits the NF-κB signaling pathway, IKKβ kinase activity was analyzed with an in-house natural product library, and CyCl was found as a potential candidate for reducing IKKβ phosphorylation. Recently, an anthocyanins-enriched extract from elderberries, in which five cyanidin-based anthocyanins were identified, inhibited proliferation and induced apoptosis in melanoma cells [33]. Cyanidin-3-O-glucoside, a cyanidin derivative, inhibited NF-κB signaling molecules and had a protective effect through activation of the Nrf2 pathway in intestinal epithelial cells exposed to TNF-α [34].…”
Section: Discussionmentioning
confidence: 99%
“…activation via loss of mitochondrial membrane potential [81]. Many other studies have also proved the antiproliferative and proapoptotic effects of anthocyanins on melanoma or others skin diseases [82][83][84]. Our latest published revealed that anthocyanins may inhibit melanoma cell proliferation, increase the level of oxidative stress, and diminished mitochondrial membrane potential [84].…”
Section: Skin Cancermentioning
confidence: 95%
“…Reactive oxygen species (ROS) are produced by all aerobic cells and are important to the immune system, cell signaling, and many other normal body functions. They can elicit cellular damage, leading to degenerative diseases such as inflammation, cardiovascular disease, cancer, and aging if ROS are excessively produced [33][34][35]. As we mention previously, anthocyanins are potent antioxidants and their effectiveness has been tested in vitro and in vivo.…”
Section: Anthocyanins' Potential Health Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, apoptosis is the mechanism through which many anti-cancer treatments, including melanoma treatments, work. Some common cosmetic ingredients, such as elderberry extract, can enhance effectivity of cancer treatment by enhancing apoptosis in malignant cells [ 47 ].…”
Section: Ghk and Gene Expressionmentioning
confidence: 99%